Effect of Cu addition on the microstructures and properties of ultrafine Ti(C, N)-based cermet. (November 2020) - Xu, L.W.; Lin, N.; Ma, C.; Wang, Z.Y.; Kang, X.Y.; He, Y.H.
Abstract: In this work, the microstructure, mechanical properties, corrosion behavior and wear resistance of ultrafine Ti(C, N)-based cermet containing different Cu contents were characterized by scanning electron microscope, X-ray diffraction, transmission electron microscope, mechanical testing, wear experiment, Tafel extrapolation and EIS measurements. The results showed that the Cu additions could enter into the binder phase and form the solid solution, hindering the grain growth of hard phase by inhibiting the dissolution and precipitation process. With increasing Cu content in cermet, the hardness of cermet increased from 92.3HRA to 92.7HRA, and the fracture toughness increased firstly and then decreased. The hardness and fracture toughness of cermet containing 1.0 wt% Cu were 92.5 HRA and 10.70 MPa m 1/2, respectively. The addition of Cu could improve the corrosion resistance of cermet in 1 mol/L HCl solutions through reinforcing binder phase. Additionally, Ti(C, N)-based cermet with Cu addition demonstrated an enhanced wear resistance. Highlights: The ultrafine Ti(C, N) based cermets with the various Cu content were fabricated. The addition of Cu element inhibits the growth of hard phase during sintering process. The addition of Cu element improves mechanical properties and corrosion resistance obviously. The cermets with Cu addition have a great potential in machining tools.